Some Cautions on the US Model of Assessment in Engineering and Science - Hoole, D.; Hoole, S.R.H. (Faculty of Science, University of Jaffna, 2011)
The US model of assessing students is increasingly widespread and is pushed through so called reform efforts. This model includes take-home exams, homework and group work where the independence of the student’s work cannot be authenticated and is bankrolled worldwide by agencies such as the World Bank and the ADB under US influence. This paper surveys the extensive literature on academic cheating dating from the 1960s, confirms through a survey that the prevalent situation is unchanged and explains how the model works in real life, to serve as a warning to systems that blindly emulate the US model of assessment. The particular applicability of these observations to science and engineering courses is noted.
Keywords: Take-home exams; ethics; faculty assessments; curricular uniformity; grading